CONGENITAL EPIDERMOLYSIS BULLOSA: PECULIARITIES OF EPIDERMIS REGENERATION AND METHODS OF TREATMENT - А. A. Kubanov; A. EH. Karamova; V. I. Al'banova; V. V. CHikin; E. S. Monchakovskaya (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Congenital epidermolysis bullosa is a group of hereditary skin diseases caused by mutations in the genes of structural proteins of the dermoepidermal junction of the skin, characterized by formation of blisters and erosions at the smallest mechanical trauma. In patients with severe subtypes of borderline and dystrophic epidermolysis bullosa there are long-term erosive and ulcerative defects with disruption of the healing process. Factors that impede healing include: malnutrition, anemia, pain, inactivity, local factors (presence of infection, prolonged inflammation, extensive nature of the lesion, absence of skin appendages in the affected area, deficiency or lack of formation of type VII collagen). Elimination of healing impeding factors is the main challenge in treatment of severe subtypes of bullous epidermolysis. Modern promising treatment techniques are at the stage of development and have not yet been introduced into clinical practice, and, as of today, skin care and optimal topical treatment with modern non-adhesive dressings remain the most widespread treatment methods that facilitate accelerated healing.